2011
DOI: 10.1007/s12017-011-8144-z
|View full text |Cite
|
Sign up to set email alerts
|

No Association of LOXL1 Gene Polymorphisms with Alzheimer’s Disease

Abstract: Aggregation of amyloid-beta is one of the major characteristics in brains of patients with Alzheimer's disease (AD). Although several mechanisms behind the formation of such aggregates have been suggested the regulatory factors are still unknown. The present study aimed at investigating the association of lysyl oxidase-like 1 (LOXL1) polymorphisms with AD diagnosis and cerebrospinal fluid biomarkers (CSF) for the disease. Proteins of the lysyl oxidase (LOX) family are involved in cross-linking extracellular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
7
0
2
Order By: Relevance
“…27,30 These associations also provide justification for the SIFT and PolyPhen-2 results predicting disease-causing amino acid substitutions based on sequence and structural changes. Similar to our results, other studies of LOXL1 SNPs found no significant association with Alzheimer's disease 31 or adolescent idiopathic scoliosis, 32 despite suggestive evidence from studies of animal models. 33,34 LOXL1's cross-linking elastin has been suggested to be a mechanism for vessel stability and therefore protective during development of vascular disease such as abdominal aortic aneurysm.…”
Section: Discussionsupporting
confidence: 89%
“…27,30 These associations also provide justification for the SIFT and PolyPhen-2 results predicting disease-causing amino acid substitutions based on sequence and structural changes. Similar to our results, other studies of LOXL1 SNPs found no significant association with Alzheimer's disease 31 or adolescent idiopathic scoliosis, 32 despite suggestive evidence from studies of animal models. 33,34 LOXL1's cross-linking elastin has been suggested to be a mechanism for vessel stability and therefore protective during development of vascular disease such as abdominal aortic aneurysm.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, a polymorphism of the LOXL1 gene, which is strongly associated with PEX, is lacking in AD. 31 Therefore, several gene polymorphisms influence a range of diseases of similar groups in different ways, and their effects do not always reflect the molecular mechanisms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…) populations, Alzheimer's disease in a Swedish population (Abramsson et al. ), and cardiovascular disease in a Hungarian population (Hollo et al. ), although none, except for the study of Fuse et al.…”
Section: Discussionmentioning
confidence: 99%
“…) and systemic (Abramsson et al. ; Hollo et al. ) pathologies to determine an association between EX and these pathologies, some suggesting that LOXL1 variants may be disease markers for EX.…”
Section: Introductionmentioning
confidence: 99%